Transformation of asphaltenes of vacuum residues in thermal and thermocatalytic processes - Akimov, Akim S. (Petroleum science and technology)
The work deals with the study of high molecular weight components of oils, namely with asphaltenes. The relevance of research aimed at studying the structural changes and thermal properties of asphaltenes under the conditions of heavy residual feedstock processing increases every year. It has been shown that the addition of NiCr-WC promotes the retardation of gas formation and an increase in the destruction of resins and asphaltenes of the vacuum residue.The average diameter of the aromatic layers (La) increases from 8.10 to 10.58 Å in the cluster and decreases the number of aromatic layers in a cluster (M) and the average height of a cluster of aromatic layers (Lc) from 7.58 to 5.09 and 26.70 to 18.34Å respectively in the series ‘initial asphaltenes – asphaltenes after thermal processing – asphaltenes after thermocatalytic processing. Based on differential scanning calorimetry in the temperature range 400–700 C, the destruction of asphaltenes is accompanied not only by the formation of low molecular weight hydrocarbon structures but the intensive removal of heteroatoms (S and N).